Hybrid virtual polarimetric massive MIMO measurements at 1.35 GHz. Issue 15 (30th May 2019) - Challita, Frédéric; Laly, Pierre; Liénard, Martine; Tanghe, Emmeric; Joseph, Wout; Gaillot, Davy P.
Abstract : The polarimetric massive multiple‐input multiple‐output (MIMO) radio channel of an indoor line‐of‐sight scenario is investigated at 1.35 GHz using a real‐time radio channel sounder. The 8 × 12 massive MIMO transmitter is constructed using a hybrid architecture including a vertical uniform linear array translated at different horizontal positions forming a virtual, yet realistic, uniform rectangular array. The performance of the system is evaluated with six users distributed in the room for different polarisation schemes and receiver orientations using propagation channel‐based metrics (such as receiver spatial correlation and Rician factor) and system‐oriented metrics such as sum‐rate capacity and signal to interference and noise ratio. The results show a clear dependence of the performance to the polarisation schemes and receiver orientation and showing that when facing the array, cross‐polarisation can be very beneficial. Furthermore, it is concluded that the additional degree of freedom brought by the polarisation diversity can contribute to improve spectral efficiency (∼20% depending on the configuration), paving the way for further capacity enhancements in massive MIMO systems. It was also found that the receiver spatial correlation can be modelled using a Burr distribution.